Pengaruh Model Pembelajaran Cooperative Tipe Teams Games Tournament Dalam Meningkatkan Motorik Kasar Melalui Permainan Olahraga Tradisional - Daniarti, Railyta Rachmiana; Sonjaya, Azhar Ramdhana; Hermawan, Irwan; Permadi, Asep Angga (Jurnal Porkes, 2025)
This study aims to examine the effect of the cooperative model of teams games tournament in improving the gross motor skills of students through traditional sports games. The research method used is a quasi-experimental design. The design used is a nonequivalent control group design. The population used is students from SDN 3 Maripari with a total of 120 students. The sample taken is a fourth-grade class consisting of 20 students, with the sampling technique using purposeful sampling. The research instrument is in the form of the Test of Gross Motor Development 2 (TGMD 2). Data analysis techniques used descriptive statistical analysis and parametric statistical analysis. Descriptive statistical analysis was used to calculate the pretest and posttest scores of students' gross motor skills, while parametric statistical analysis used the independent sample t-test. The results showed that the n-gain of the experimental group (57.50) was greater than that of the control group (15.60). The control group used the DI model with a pretest score of 63.1 and a posttest score of 78.7, while the experimental group used the TGT model with a pretest score of 75.4 and a posttest score of 132.9. Therefore, it can be concluded that the gross motor skills of students in the class using the Times Games Tournaments model were better than those in the class using the Direct Instruction learning model.